Analysis of the Utilization of Spraying Drones in Labulang Hamlet Farmer Groups in Patobong Village, Mattiro Sompe District - Firdaus; Alimuddin Sa’ban Miru; Nurhaliza Munir (Journal of Embedded Systems, Security and Intelligent Systems, 2024)
This study aims to determine the analysis of the use of drone sprayers in farmer groups which includes a description of the use of drones, the level of knowledge and the level of motivation of farmers both individually and together. This research consists of 4 main stages including: observation, determining research variables, data processing and drawing conclusions. Data collection was carried out using observation, interview and questionnaire techniques. To find out the results of the study, data analysis techniques were carried out, namely: multiple linear regression, hypothesis testing, namely the t test and F test. The number of samples involved was 32 people. The results showed that: 1) the type of Spraying drone used in the field is DJI Agras T40 with a payload capacity of 20 liters. 2) The level of knowledge of farmers has two criteria, namely high and medium. The farmers with a high level of knowledge amounted to 34.3% and those with a moderate level of knowledge amounted to 65.6%. 3) The level of motivation of farmers has three criteria, namely high, medium and low. The farmers who have a high level of motivation amounted to 12.5%, a moderate level of motivation amounted to 31.3% and a low level of motivation amounted to 56.3%.4) Based on the results of the t test and the F test, it shows that the level of knowledge and the level of motivation have a significant effect on the use of drone spraying in Labulang Hamlet, Patobong Village, Mattiro Sompe District, so that H1 independent variables are "accepted" on the dependent variable and H0 is rejected.